생체모사환경에서 DLC 필름의 부식마모 특성에 미치는 Si함량의 영향에 관한 연구 - 김호건; 김정구; 박세준; 이광렬; 김우중 (대한금속·재료학회, 2005)
In a method to improve resistance to wear, corrosion and mechanical properties of protective coating, DLC coatings have been extensively studied over the past several years due to their unique combination of properties.Especially, Si-DLC coatings have been attracting increasing interest of researchers since they have a great potential for solving some of the major disadvantages of pure DLC coatings. Si-incorporated diamond-like carbon (Si-DLC)coatings ranging from 0 to 2 at.% were deposited on Ti alloy substrate by means of r.f. plasma-assisted chemical vapor deposition (r.f. PACVD) technique, using mixtures of benzene (C6H6) and silane (SiH4) as the reaction gases. Corrosion and wear behavior of DLC coatings was investigated by lectrochemical techniques (potentiodynamicpolarization test and electrochemical impedance spectroscopy), tribological techchnique(wear test) and surface analyses (atomic force microscopy, scanning electron microscopy and Raman spectroscopy). It was found that DLC coatings with increasing Si content could acquire improved corrosion and wear resistance in the simulated body fluid environment (0.89 wt.% NaCl of pH 7.4 at 37oC).